Functional and radiological outcome of comminuted shaft of humerus fracture treated by dynamic compression plate - Raja K. V., Bharathi; Ram, Ganesh G. (International Journal of Research in Orthopaedics, 2018)
Background: Humeral shaft fractures represents between 3% and 5% of all fractures of which a certain number of patients require surgical intervention. This study aims to determine the efficacy of dynamic compression plate in the treatment of humeral shaft fractures. Methods: A prospective study was carried out over a period of 2 years in Sri Ramachandra Medical College, Chennai including 30 cases of shaft of humerus fractures treated by open reduction and internal fixation using Dynamic Compression plate among which both comminuted and segmental closed shaft of humerus fractures were included. While open fractures and ipsilateral forearm and clavicle fractures were excluded. AO classification was used to classify the fractures and the average follow up period was two years. The American Shoulder and Elbow Surgeons (ASES) shoulder score and Romen al series grading were used. Results: We had 93.3% excellent/good result and 6.7% poor results. In our series we had one non-union, one delayed union and one case of deep infection. Conclusions: Proper preoperative planning, minimal soft tissue dissection, strict asepsis, proper postoperative rehabilitation and patient education were essential to obtain excellent results. Early post-operative mobilization following rigid fixation of the fracture of humerus, with DCP lowered the incidence of stiffness and sudecks dystrophy.